Expansin-mediated developmental and adaptive responses: A matter of cell wall biomechanics? - Samalova, Marketa; Gahurova, Evelina; Hejatko, Jan (Quantitative plant biology, 2022)
Biomechanical properties of the cell wall (CW) are important for many developmental and adaptive responses in plants. Expansins were shown to mediate pH-dependent CW enlargement via a process called CW loosening. Here, we provide a brief overview of expansin occurrence in plant and non-plant species, their structure and mode of action including the role of hormone-regulated CW acidification in the control of expansin activity. We depict the historical as well as recent CW models, discuss the role of expansins in the CW biomechanics and address the developmental importance of expansin-regulated CW loosening in cell elongation and new primordia formation. We summarise the data published so far on the role of expansins in the abiotic stress response as well as the rather scarce evidence and hypotheses on the possible mechanisms underlying expansin-mediated abiotic stress resistance. Finally, we wrap it up by highlighting possible future directions in expansin research.
Keywords: cell wall loosening; biomechanics; plant; expansin; development; cell wall remodelling